Ultrafast Double Pulse All-Optical Reswitching of a Ferrimagnet - Coey, John; Stamenov, Plamen; Rode, Karsten; Atcheson, Gwenael (My University, 2021)
All-optical reswitching has been investigated in the half-metallic Heusler ferrimagnet Mn2Ru0.9Ga, where Mn atoms occupy two inequivalent sites in the XA-type structure. The effect of a second 200 fs, 800 nm laser pulse that follows the first pump pulse, when both are above the threshold for switching, is studied as a function of t12, the time between them. Aims were to determine the minimum time needed for reswitching and to identify the physical mechanisms involved. The time trajectory of the switching process on a plot of sublattice angular momentum, S4a vs S4c, is in three stages; when t<0.1  ps, the sublattice moments are rapidly disordered, but not destroyed, while conserving net angular momentum via optical spin-wave excitations. This leads to transient parallel alignment of the residual Mn spins in the first quadrant. The net angular momentum associated with the majority sublattice then flips after about 2 ps, and a fully reversed ferrimagnetic state is then established via the spin-lattice interaction, which allows reswitching provided t12>10  ps.
PUBLISHED
Keywords: Magnetization switching; Ultrafast magnetic effects; Ultrafast magnetization dynamics; Nanoscience & Materials; FABRICATION; NANOSTRUCTURES; Nanotechnology; Physics